Not Your Cup of Tea?: How Interacting With a Robot Can Increase Perceived Self-efficacy in HRI and Evaluation - Rosenthal-von der Pütten, Astrid Marieke; Bock, Nikolai; Brockmann, Katharina (2017 12th ACM/IEEE International Conference on Human-Robot Interaction (HRI, 2017)
The goal of this work is to explore the influence of do-it-yourself customization of a robot on technologically experienced students and unexperienced elderly users' perceived self-efficacy in HRI, uncertainty, and evaluation of the robot and interaction. We introduce the Self-Efficacy in HRI Scale and present two experimental studies. In study 1 (students, n=60) we found that any interaction with the robot increased self-efficacy, regardless of whether this interaction involves customization or not. Moreover, individual increases in self-efficacy predict more positive evaluations. In a second study with elderly users (n=60) we could not replicate the general positive effect of the interaction on self-efficacy. Again, we did not find the hypothesized stronger effect of customization on self-efficacy, nor did we find that relationship between self-efficacy increase and evaluation. We discuss limitations of the setting and for questionnaire design for elderly participants.